Panorama regional da educação infantil no Sudoeste do Paraná: análise da organização do atendimento municipal à criança de 0 a 5 anos - Amann, Wilian (2023)
This dissertation is linked to the Culture, Educational Processes and Teacher Training research line, of the Postgraduate Program in Education in Francisco Beltrão at a master's level (PPGEFB) at the State University of Western Paraná (UNIOESTE) and to the group of Education, children and infancy research (GPECI), linked to the same institution mentioned above. Its theme is the organization of early childhood education in the Southwest of Paraná State, based on the understanding that the debate on the implementation of laws that guarantee the right to quality education for children in this age group is important, current and necessary so that respect and consolidation of laws in practice will be present in the municipalities across the country. The research analyzes the organization of public early childhood education services for children aged zero to five in the municipalities of the region mentioned, emphasizing how national and state policies at this stage of education are reflected in the organization of the municipalities that comprises it. This way, it presents updated data from this region, regarding organizational, administrative, pedagogical aspects, as well as management teams and early childhood education professionals in municipal networks. It seeks to contribute to the debate on this stage of teaching, and can also serve as a guide for new research in the area. It is a study with a qualitative and quantitative approach of an exploratory nature. The set of data analyzed was composed from an online questionnaire sent to all municipalities of the region researched, complemented with information extracted from the “2021 microdata” and “Synopsis - basic education statistics 2022” files that make up the school census files, available by the MEC through the official INEP website. As a result, we found a diversity of realities: some municipalities comply with current laws and regulations, but not all of them. And we understand there are omissions, contradictions, weaknesses, and possible mistakes in the municipal education networks of the municipalities researched in terms of guaranteeing the application of all public policies for this educational stage